Debt, poverty and resource management in a rural smallholder economy - Edward B. Barbier; Ramón López (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper explores the link between poverty and resource allocation, including the management of natural resources, by chronically indebted rural smallholders in developing countries. The paper proposes a formal intertemporal model of a credit constrained farm household that can invest in wealth accumulation to relieve its long run indebtedness or conserve resources. The household must decide on an optimal combination of investments in the two forms of capital, given their savings capacity, indebtedness and costs of obtaining credit. The evolution of the natural resource base is closely dependent on the investment strategy followed by the household. The model is also used to analyse how policy-related variables may affect the household's investment strategy and, consequently, resource management and household poverty: (i) Changes in output and input prices, and (ii) changes in the liquidity available in rural credit markets.
Keywords: Q0; Q2; O1; 330; Debt; Developing country; Intertemporal model; Poverty; Pricing policies; Resource management; Rural credit; Rural households; Smallholders; Wealth accumulation; Rohstoffpolitik; Kleinbäuerliche Landwirtschaft; Armut; Schulden; Agrarkredit; Intertemporale Allokation; Investitionsentscheidung; Theorie; Entwicklungsländer